CONJOINED TWINS PRESENTING AS HAND PROLAPSE IN A RURAL HOSPITAL: A CASE REPORT - JD, Usman; AD, Zagga; A, Bello; M, Faruku; MA, Musa (Medico Research Chronicles, 2015)
Conjoined twin pregnancies are so rare and maybe ones in a lifetime experience. Therefore there is so much to learn from each case. We present a case of male thoraco-omphalopagus conjoins twin, Nigerian that presented as a case of hand prolapsed diagnosed only after cesarean section. Both twins were stillborn. Conjoined twin pregnancy is a rare occurrence and may poise some obstetric challenges. Since many congenital defects can now be detected before birth, this place high importance in antenatal care and prenatal diagnosis as to determine the mode of delivery and early termination of pregnancy when the anomaly is not compatible with life.